Erythroxylum confertifolium, a new species from Chapada dos Veadeiros National Park, Goiás, Brazil, unveiled by morphology and leaf anatomy - Da Silva, Marcos José; Dos Santos, Igor Soares [UNESP] (Magnolia Press, 2023)
Erythroxylum confertifolium, a new species from the Chapada dos Veadeiros National Park, Goiás, Brazil, is described and illustrate here. It differs from E. campestre and E. parvistipulatum, its most similar congeners, by a set of morphological (e.g. branching appearance of the stem, leaf shape and consistency, numbers of setules of stipules and cataphylls, aspect of the pedicel, size of flower parts and fruits, and aspect of auricles of petals and styles), and leaf anatomical characters (e.g. number of main and accessory vascular bundles and their appearance on the petiole and midrib, aspect of the sheath that surrounds the vascular bundle, presence or absent of papillae, palisade parenchyma/spongy parenchyma ratio, presence or absence of sheath extension in vascular bundles, as well as composition of tissues of the cortex, and fibers types in midrib). Images, conservation assessments, and a distribution map of the new species are presented, as well as images for their morphologically correlated.
Keywords: Cerrado; Diversity; Micromorphology; Wild Coca